Analisis Penentuan Tarif Jasa Rawat Inap Pada Rumah Sakit Raflesia Bengkulu - Adriansyah, Adriansyah (Sekolah Tinggi Ilmu Ekonomi H. Agus Salim Bukittinggi, 2012)
This research is aimed to identify tariff of inpatient hospital service in Raflesia Hospital Bengkulu, especially for tarif of inpatient service based on hospital management in 1997 to require hospital social service category within breakevent point of hospital profit. The analysis of tariff can be separated by hospital costs at least 1.058.686.120 rupiahs and hospital revenues at least 704.026.270 rupiahs. Percentageof hospital rooms consist of 5% (Principal VIP Class). To find out cost that spended among classes, total cost among classes divided by day for inpatient service during one year. According to result of this research there is a residual tariff, the largest residual in Class III and Class IV. In addition, hospital management require cross subsidiary fund to equalized revenues between Principal VIP Class with the others in break even analysis of inpatient hospital service.